Navigating the Student Affairs Landscape: An Autoethnographic Exploration of the Student Affairs Profession from Canadian Perspectives - Hanson, Cori; Kelly, Heather; Hameed, Sania; Ahmed, Shakeeb; Li, Katherine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
This autoethnographic study examines the evolving professional landscape of student affairs in Canada through the lived experiences of five scholar-practitioners. Drawing on reflective narratives and thematic analysis, the study explores three central themes: unplanned career entry into student affairs, the expanding and complex demands placed on practitioners, and the dynamic construction of professional identity. Framed by the job demands-resources model and social ecological systems theory, this research reveals how intersecting personal, institutional, and systemic forces may shape the careers and commitments of student affairs professionals. Findings highlight tensions between credentialism and experiential knowledge, the emotional toll of equity work, and the precarity of institutional belonging. This article offers a nuanced understanding of the student affairs profession and calls for more inclusive, relational, and critically reflexive approaches to professional development, institutional policy, and workforce sustainability. It contributes to emerging discourses on practitioner well-being, professionalization, and systemic transformation in higher education.